Influence of active layer thickness on the performance of organic photovoltaics with light trapping - Husna Amira Hassan (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
To maximize the performance of an organic photovoltaic device, the use of light trapping is necessary. In this thesis, the effect of active layer thickness on the performance of organic photovoltaic (OPV) cells with ideal light trapping is investigated. Although actual light trapping schemes are not ideal, this study can still be a useful guide to maximize the performance of actual OPVs with light trapping. In this study, the effect of active layer thickness on the power conversion efficiency (PCE), short-circuit current, open-circuit voltage and fill factor (FF) of OPVs with ideal light trapping is described. The analytical model for bulk heterojunction OPVs developed by Inche Ibrahim (2018) is used to calculate the current-voltage characteristics in order to determine the PCE, short-circuit current, open-circuit voltage and FF of OPVs with ideal light trapping. For a low-recombination-loss OPV with ideal light trapping, the active layer thickness weakly affects the PCE. For a high-recombination-loss OPV with ideal light trapping, the active layer thickness strongly affects the PCE. To maximize the PCE of high-recombination-loss OPV with light trapping, the active layer thickness must be very thin enough (around 10nm). This study proves that it is important for OPVs to have a low recombination loss so that the active layer thickness does not become a hindrance or an additional factor in creating highly efficient light trapping schemes that can maximize the PCE. This study also shows that it is equally (if not more) important to develop light trapping schemes that are highly efficient at very thin active layers (around 10nm) so that the PCE of any OPVs can be more or less maximized, whether the OPVs have low or high recombination losses. Finally, the use of uniform light absorption profile and non-uniform light absorption profile in modelling OPVs is being compared in this study. To avoid complexity, a uniform light absorption profile is usually used when modelling organic photovoltaic cells (OPVs). However, the actual light absorption profile is not uniform. It is found that a uniform light absorption profile can be used as a replacement for the actual non-uniform light absorption profile in modelling an OPV provided that the actual light absorption profile inside the OPV has a peak absorption that is roughly less than twice its average absorption. Nevertheless, the use of a uniform light absorption profile in investigating the effect of a certain parameter on the performance of OPVs should always be used with care if variations in the value of the said parameter lead to different light absorption profiles, for example when the effect of active layer thickness is investigated by varying its value.